2020
DOI: 10.1038/s41598-020-66637-y
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Peritoneal Washing Cytology-Positive Gastric Cancer without Gross Peritoneal Metastasis in Patients who Underwent Radical D2 Gastrectomy

Abstract: Background The clinical features and therapeutic strategies for gastric cancer with positive peritoneal washing cytology but without visible gross peritoneal metastasis have not been defined. The aim of this study was to evaluate the effect and clinical prognostic value of postoperative chemotherapy in gastric cancer patients with positive peritoneal washing cytology without gross peritoneal metastasis who underwent radical D2 gastrectomy in terms of disease-free survival (DFS) and overall survival (OS). Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Further, the study documented the benefit of adjuvant S-1 monotherapy, as the median survival increased to 22.3 mo compared to 11.8 mo in the surgery alone group[ 19 ]. The benefit of adjuvant therapy was confirmed in another study from Korea by Shim et al [ 20 ]. Adjuvant chemotherapy by TS-1 ± cisplatin or oxaliplatin plus capecitabine (XELOX) or oxaliplatin + 5-FU (FOLFOX) improved median disease-free survival (DFS) (11.63 vs 6.98 mo, P < 0.001) and OS (25.50 vs 12.11 mo, P < 0.001)[ 20 ].…”
Section: Upfront Surgery For Cy1 Gc Patientsmentioning
confidence: 73%
See 2 more Smart Citations
“…Further, the study documented the benefit of adjuvant S-1 monotherapy, as the median survival increased to 22.3 mo compared to 11.8 mo in the surgery alone group[ 19 ]. The benefit of adjuvant therapy was confirmed in another study from Korea by Shim et al [ 20 ]. Adjuvant chemotherapy by TS-1 ± cisplatin or oxaliplatin plus capecitabine (XELOX) or oxaliplatin + 5-FU (FOLFOX) improved median disease-free survival (DFS) (11.63 vs 6.98 mo, P < 0.001) and OS (25.50 vs 12.11 mo, P < 0.001)[ 20 ].…”
Section: Upfront Surgery For Cy1 Gc Patientsmentioning
confidence: 73%
“…The benefit of adjuvant therapy was confirmed in another study from Korea by Shim et al [ 20 ]. Adjuvant chemotherapy by TS-1 ± cisplatin or oxaliplatin plus capecitabine (XELOX) or oxaliplatin + 5-FU (FOLFOX) improved median disease-free survival (DFS) (11.63 vs 6.98 mo, P < 0.001) and OS (25.50 vs 12.11 mo, P < 0.001)[ 20 ]. No significant differences were observed between the regimen of postoperative chemotherapy and survival[ 20 ], thus the most optimal regimen remains unclear.…”
Section: Upfront Surgery For Cy1 Gc Patientsmentioning
confidence: 73%
See 1 more Smart Citation
“…Recent studies have found that positive abdominal cytology is an important factor affecting the prognosis of patients with GC ( 66 , 67 ). A recent study found postoperative chemotherapy can improve the survival rate of GC patients with positive peritoneal cytology ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…For GC patients with positive cytology, but without gross peritoneal metastases, no clear therapeutic strategies have yet been established. Studies conducted by Hyun-Jeong et al [ 24 ] have shown that postoperative chemotherapy improves the survival outcome compared to surgery alone in GC patients who underwent radical D2 gastrectomy. Since the presence of FCC in the peritoneal fluid/lavage influences further therapeutic decisions, it is important that the test result is reliable.…”
Section: Discussionmentioning
confidence: 99%